The The Impact of Global Warming on Climate Change (Systematic Literature Review) - FITRI, Fitri Permata indah; Asyifa, Najmi; Darma Putra, Fajar (Universitas Negeri Padang, 2025)
The worldwide problem of global warming is a major concern for the sustainability of life on earth. If this event is not addressed quickly, it can have dire consequences. Global warming occurs when there is a concentration of certain gases known as greenhouse gases, which continues to increase in the air, this is caused by human actions, industrial activities, especially CO2 and chlorofluorocarbons. Global warming has a broad and serious impact on the bio-geophysical environment (such as melting ice at the poles, rising sea levels, expanding deserts, increasing rain and flooding, climate change, extinction of certain flora and fauna, migration of fauna and pests. This study focuses on the impact of global warming on climate change. This research method is a literature review using a database from Google Scholar from the period 2019-2024